Entre histórias e permanências : trajetórias da vida acadêmica de estudantes negros ingressos na UFES através do sistema de reserva de vagas - Nobre, Lorrana Neves (2016)
This research analyzed the academic historical path of black university students entering the Federal University of Espírito Santo from 2013 on, the year of Federal Law no. 12,711/12 implementation. Such legislation guarantees the reservation of admission spots to higher education combining criteria of public school origin, income and ethnic-racial factor. With qualitative approach characteristics, the study, based on the investigative proposal of the methodology of thematic oral history (MEIHY, 1996), sought to give visibility to the experiences and stories experienced by the subjects about the main educational, psychological, financial demands that have arisen, and still arise, on their academic life, in order to reflect and point out possible ways to consolidate the public policies of permanence in the institution. In light of this, the semi-structured interview was selected as data collection tool. Through the investigation and analysis of the collected data, action plans were constructed to meet the main aspects pointed out by the social actors of the research regarding their permanence in the university. From the histories narrated by the participants of the research, it is concluded that for the implementation of a policy of qualitative permanence that positively interferes in its academic trajectories, it becomes necessary to maintain practical institutional mechanisms and to improve the affirmative policies of internal permanence of the university